FRONTAL REGION- AESTHETIC DEMANDS IN IMPLANT-PROSTHETIC REHABILITATION - Cretu Ionut Cosmin; Agop-Forna Doriana; Humă Mădălina; Roznov Maria-Laura; Tibeica Andreea; Camilar Maria Camelia; Forna Norina (Romanian Journal of Medical and Dental Education)
Aim of the study: This study aims to evaluate the maxillary frontal aesthetic demands in implant-prosthetic rehabilitation. Gingival contour, volume and soft tissue health are essential factors in achieving an optimal aesthetic result. Achieving a successful aesthetic result for restoration on implants involves not only the surgical phase, but also the crucial prosthetic phase. Prosthetic considerations include both the design of the implant restoration and the management of the peri-implant soft tissues.